PROBLEMATIKA PENERAPAN HUKUM PIDANA ISLAM DI INDONESIA - Adi Syahputra Sirait (IAIN Padangsidimpuan, 2022)
This paper aims to analyze how problematic the application of Islamic criminal law in Indonesia is. This type of research is to use an explanative mix method. The source of data from this research is the perception or view of the people of Medan city which consists of ordinary people, students and community leaders. Data collection methods were carried out by distributing questionnaires, focus group discussions and interviews, data analysis was carried out by coding, categorizing, tabulating, testing data and ending with conclusions. The results of this study indicate that at the level of ordinary people there is ignorance and lack of understanding of Islamic Criminal Law (Jinayah), then at the student level the view that there is a sadistic image attached to Islamic criminal law so that it is not easy to apply and at the level of community leaders the view that the Indonesian paradigm It is not an Islamic state that is firmly attached so that it is difficult to change, coupled with the condition of the plural and multicultural Indonesian society.